2020
DOI: 10.18196/jmmr.92124
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Readiness Assessment for Disasters Using the Hospital Safety Index in Several Accredited Hospitals in Yogyakarta Province

Abstract: Indonesia is a disaster-prone country, so research on hospital preparedness for disasters is necessary. One of the tools to measure the readiness of hospitals in facing disasters using the Hospital Safety Index (HSI) from WHO. This study aims to determine the readiness of hospitals to deal with disasters using HSI. Research location in PKU Yogyakarta, PKU Bantul, PKU Kotagede, PKU Nanggulan, and PKU Wonosari. These PKU that have been accredited by the Hospital Accreditation Committee in Yogyakarta Province. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…The findings of this study are in line with literature explaining the low level of structural safety due to the lack of knowledge, lack of norms, and budgetary shortfall 13,[22][23][24][25][26][27] , thus raising awareness about the importance of maintaining good structural safety of the facility, providing resources (mainly guidelines) and updating the knowledge of technical personnel in charge of structural components of the facility are some of the possible solutions. In addition, most of the UHs included in this study have had several expansions throughout the years, which has been proven to be one of the major causes to reduce structural safety, as it does not necessarily take into account the nature of the surrounding land and its vulnerability to natural hazards 26 . This, in Tunisia, is mainly due to lack of structured furfur planning and well performed study of needs.…”
Section: Structural Safetysupporting
confidence: 86%
“…The findings of this study are in line with literature explaining the low level of structural safety due to the lack of knowledge, lack of norms, and budgetary shortfall 13,[22][23][24][25][26][27] , thus raising awareness about the importance of maintaining good structural safety of the facility, providing resources (mainly guidelines) and updating the knowledge of technical personnel in charge of structural components of the facility are some of the possible solutions. In addition, most of the UHs included in this study have had several expansions throughout the years, which has been proven to be one of the major causes to reduce structural safety, as it does not necessarily take into account the nature of the surrounding land and its vulnerability to natural hazards 26 . This, in Tunisia, is mainly due to lack of structured furfur planning and well performed study of needs.…”
Section: Structural Safetysupporting
confidence: 86%
“…Although it is estimated that the HSI has been used to assess the safety of more than 3500 facilities worldwide [ 6 ], scientific publications on it are scant. Most of the studies found in the literature refer to a few countries, and they are either reporting the results of HSI assessments [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ], comparing preparedness across cities [ 17 ], or adapting the tool to specific contexts [ 18 , 19 , 20 ]. There is a lack of studies on the methodological implications of using the HSI as a primary data collection tool and a shortage of qualitative studies.…”
Section: Introductionmentioning
confidence: 99%